2019
DOI: 10.3390/rs11070877
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Quality Assessment of Pan-Sharpened Images

Abstract: Pan-sharpening (PS) is a method of fusing the spatial details of a high-resolution panchromatic (PAN) image with the spectral information of a low-resolution multi-spectral (MS) image. Visual inspection is a crucial step in the evaluation of fused products whose subjectivity renders the assessment of pansharpened data a challenging problem. Most previous research on the development of PS algorithms has only superficially addressed the issue of qualitative evaluation, generally by depicting visual representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…Other quality metrics have been proposed in [14], which adopts the spectral distortion borrowed from [11] and the spatial distortion based on the natural image quality evaluator model, and in [15], which presents a perceptual quality index.…”
Section: Quality Assessment Of Pansharpened Images a Backgroundmentioning
confidence: 99%
“…Other quality metrics have been proposed in [14], which adopts the spectral distortion borrowed from [11] and the spatial distortion based on the natural image quality evaluator model, and in [15], which presents a perceptual quality index.…”
Section: Quality Assessment Of Pansharpened Images a Backgroundmentioning
confidence: 99%
“…Xia et al [18] reviewed and concluded the quality assessment for remote sensing images. Agudelo-Medina [19] proposed a new IQA measure that supports the visual qualitative analysis of pan-sharpened outcomes by using the statistics of natural images (commonly referred to as natural scene statistics), to extract statistical regularities from pan-sharpened images. A no-reference hyperspectral IQA method based on quality-sensitive features extraction was presented by Jingxiang [20].…”
Section: Related Work and Novelties And Necessity Of The Studymentioning
confidence: 99%
“…The restoration of the edge component deteriorates when external noise is introduced. In this paper for numerical analysis we have considered performance metrics like Entropy (E), Correlation coefficient (ℂ), Local texture energy (ℓ) , peak signal to noise ratio (PSNR) and structural similarity index measure (SSIM) [34][35][36][37][38]. Entropy ( ) is the information content of image and it is represented as…”
Section: B Edge Sharpness Metricmentioning
confidence: 99%
“…Local texture energy (ℓ) is an image quality assessment parameter that measures distortions affecting the image textures [34,35]. We have used this metric to measure any impairment caused by contrast or edges.…”
Section: B Edge Sharpness Metricmentioning
confidence: 99%